2021
DOI: 10.1101/2021.10.28.466378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stratification of the Gut Microbiota Composition Landscape Across the Alzheimer’s Disease Continuum in a Turkish Cohort

Abstract: Alzheimer’s disease (AD) is a heterogeneous neurodegenerative disorder that spans over a continuum with multiple phases including preclinical, mild cognitive impairment, and dementia. Unlike most other chronic diseases there are limited number of human studies reporting on AD gut microbiota in the literature. These published studies suggest that the gut microbiota of AD continuum patients varies considerably throughout the disease stages, raising expectations for existence of multiple microbiota community type… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Due to the lower levels of these compounds found in older adults on cholinesterase inhibitors, it could be proposed that these medications may prevent absorption or increase metabolism of CAP TTs. Alternatively, persons with cognitive impairment may have an altered gastrointestinal flora or delayed absorption due to the state of their disease (Nagpal et al, 2020;Doifode et al, 2021;Yıldırım et al We observed a near 2-fold increase in C max and AUC (0-12) between the doses, reaching significance for AA, and slight variability in T max and T 1/2 from 2 to 4 g, although the difference was not significant (Table 7). The slight delay in T max could be due to the rate of biotransformation of AS to AA being dependent on plasma AA concentration levels (Grimaldi et al, 1990).…”
Section: Pharmacokinetic Trialmentioning
confidence: 76%
“…Due to the lower levels of these compounds found in older adults on cholinesterase inhibitors, it could be proposed that these medications may prevent absorption or increase metabolism of CAP TTs. Alternatively, persons with cognitive impairment may have an altered gastrointestinal flora or delayed absorption due to the state of their disease (Nagpal et al, 2020;Doifode et al, 2021;Yıldırım et al We observed a near 2-fold increase in C max and AUC (0-12) between the doses, reaching significance for AA, and slight variability in T max and T 1/2 from 2 to 4 g, although the difference was not significant (Table 7). The slight delay in T max could be due to the rate of biotransformation of AS to AA being dependent on plasma AA concentration levels (Grimaldi et al, 1990).…”
Section: Pharmacokinetic Trialmentioning
confidence: 76%